Delineation of the subunit composition of human proteasomes using antisera against the major histocompatibility complex-encoded LMP2 and LMP7 subunits. - Patel, S D (1994)
The products of the Lmp2 and Lmp7 genes located in the major histocompatibility complex (MHC) class II region are postulated to form part of the proteasome complex. This large, multisubunit complex forms the major, nonlysosomal proteolytic machinery for the degradation of endogenous proteins and has been suggested to play a role in the processing of antigens presented by MHC class I molecules. The role of the MHC-encoded subunits within the proteasome has however remained enigmatic. To study this role, we have raised antibodies to recombinant LMP2 and LMP7 proteins. Under denaturing conditions, the anti-LMP7 serum recognizes one subunit of proteasome, whereas the anti-LMP2 serum recognizes two subunits, which may represent different forms of LMP2. The specificity of these sera has been ascertained by a lack of reactivity in T2 cells, which lack both genes. Furthermore under native conditions the anti-LMP2 serum immunoprecipitates a complex that is similar to proteasome but lacks several subunits, including LMP7. Preclearing experiments using this serum and a monoclonal antibody (2-17) specific for the non-MHC-encoded C2 proteasome subunit demonstrate that the complexes recognized by these two sera are distinct and that four subunits are unique to the complex precipitated by the anti-LMP2 serum. Interestingly, the different forms of LMP2 are segregated between these complexes. The relationship of the two complexes is discussed.